The Ideal Model of Intercultural Communication of the World’s Oppressed from the Perspective of the Holy Quran - Muhammad Sadeq Nasrollahi; Muhammad Reza Koohkan (آموزه‌های قرآنی, 2020)
Despite the wide differences of humans in religion, language, customs, nationality, race, color, etc., at first glance, it seems that convergence between cultures and their extensive and constructive interaction is difficult or impossible. In this study, we seek to answer the question of whether the formation of a global front of the oppressed is acceptable to the Qur'an or not? What is the desired model of intercultural communication of the oppressed and what are the principles governing it? For this purpose, a number of selected verses were analyzed by the foundation data method and its paradigm model was obtained. “Anti-arrogance as a common culture and identity of the oppressed of the world” became the main phenomenon and its causes, contexts, intervening conditions, strategies of interaction/mutual interaction and its consequences were extracted from selected verses. According to this model, the oppressed have levels, types and conditions, and the connections between them are extensive (broad) but equivocal. In other words, this front is trans- school of thought (maḏhab, doctrine), trans-religious and trans- method, but the type of relationship with each of them is different and depends on the degree of true faith of individuals. Also in these communications, there are principles that act as governing principles, and in fact, all these principles can be placed under the principle of justice. The action strategies of the Muslims on the side of the oppressed, in fact, explain the rights of each group to which it should be granted.